Applying the new corrugated steel plate (NCSP) liner in the seasonally frozen tunnel to enhance the insulation capacity of linings - Guangyao Cui; Jianfei Ma; Daoyuan Wang (Case Studies in Thermal Engineering, 2021)
Frost damages of the tunnel in cold and seasonally frozen areas seriously affect its operation safety and service life. To better prevent frost damages in seasonally frozen areas, a new corrugated steel plate (NCSP) liner is proposed to improve the insulation capacity of tunnel linings. Firstly, design parameters and construction technologies of the NCSP liner are introduced. Then, taking the Yushuchuan tunnel in Jinlin Province of China as a background, numerical models were built to explore temperature fields of the tunnel with the NCSP liner, and the theoretical insulation effect of NCSP liner was obtained. Afterwards, a field test with a duration of four years in the Yushuchuan area was conducted to verify temperature field results and the effectivity of the NCSP liner. The results show that the freezing-line moves from surrounding rock to secondary lining after the NCSP liner is adopted, and no frost damage has been found again in the four-year field test. The thermal insulation performance of seasonally frozen tunnels has been dramatically improved with the application of the NCSP liner. The conclusion of this paper can provide a scientific reference for the prevention and control of the frost damage of tunnels in seasonally frozen areas.